2015
DOI: 10.1016/j.infbeh.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between maternal and infant cortisol varies by breastfeeding status

Abstract: Objective The objective of this study was to examine associations of mother and infant salivary cortisol, measured three times over the course of a day, and assess whether these varied by breastfeeding status. Methods We conducted a cross-sectional study of 54 mothers and their infants aged 4–11 months. Mothers collected their own saliva and that of their infants upon awakening, 30 min after waking and at bedtime. Breastfeeding status was reported by mothers and cortisol level was measured in saliva in μg/dl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 33 publications
0
18
1
1
Order By: Relevance
“…At Cebu, our finding that cortisol levels were lower among women in the postpartum period relative to those who were pregnant is consistent with prior research (Conde & Figueiredo, 2014; Jung et al, ; Kulski & Hartmann, ; Patacchioli et al, ). However, our finding for suppressed cortisol levels among breastfeeding women has not been consistently reported in past studies (Ahn & Corwin, ; Benjamin Neelon et al, ; Taylor et al, ; Thanh Tu et al, ; Tu, Lupien, & Walker, ), and to our knowledge no prior study has evaluated variation in diurnal cortisol profiles in relation to breastfeeding status at different postpartum stages. At Cebu, morning cortisol was significantly lower among breastfeeding mothers for the first two postpartum periods (up to one year), but not thereafter.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…At Cebu, our finding that cortisol levels were lower among women in the postpartum period relative to those who were pregnant is consistent with prior research (Conde & Figueiredo, 2014; Jung et al, ; Kulski & Hartmann, ; Patacchioli et al, ). However, our finding for suppressed cortisol levels among breastfeeding women has not been consistently reported in past studies (Ahn & Corwin, ; Benjamin Neelon et al, ; Taylor et al, ; Thanh Tu et al, ; Tu, Lupien, & Walker, ), and to our knowledge no prior study has evaluated variation in diurnal cortisol profiles in relation to breastfeeding status at different postpartum stages. At Cebu, morning cortisol was significantly lower among breastfeeding mothers for the first two postpartum periods (up to one year), but not thereafter.…”
Section: Discussioncontrasting
confidence: 69%
“…Working with the same sample, the authors reported that the CAR was unrelated to breastfeeding status (Thanh Tu, Walker, & Lupien, ). Diurnal cortisol was not associated with breastfeeding status in other studies assessing cortisol at 7.5 weeks and 4–11 months postpartum (Benjamin Neelon et al, ; Taylor, Glover, Marks, & Kammerer, ). More recently, a study found that morning cortisol was higher at 6 months postpartum among women who breastfed, but no differences were found in either the CAR or other measurements across the day (Ahn & Corwin, ).…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Physiological attunement reflects the idea that maternal and infant physiological systems, including the HPA axis, are in sync (Bright, Granger, & Frick, ; Hibel, Granger, Blair & Finegood, ; van Bakel & Riksen‐Walraven, ). Indeed, it is well established that maternal and infant basal and diurnal cortisol levels are related (Benjamin Neelon, Stroo, Mayhew, Maselko, & Hoyo, ; Bright et al, ; Clearfield, Carter‐Rodriguez, Merali, & Shober, ; Fuchs, Möhler, Resch, & Kaess, ; Middlemiss, Granger, Goldberg, & Nathans, ; Spangler, ; Stenius et al, ). Physiological attunement has been suggested to have evolutionary roots, as it is adaptive for mothers and infants to pick up on each other's cues to external risk, resulting in attuned physiological stress.…”
Section: Introductionmentioning
confidence: 99%
“…This is a plausible scenario because previous work has shown that maternal hormones such as cortisol and oxytocin are: (1) stable in breast milk and (2) can be transferred to the gastric contents and blood plasma of the offspring upon suckling (Peaker and Neville 1991;Takeda et al 1986). Indeed, a recent study compared breastfed infants and formula-fed infants and found a significant correlation in night cortisol levels between mothers and infants only for the breastfeeding dyads (Neelon et al 2015). Future work is needed in which cortisol and oxytocin levels are directly examined in breast milk and saliva to test this possibility.…”
Section: Discussionmentioning
confidence: 99%